Relationship between nutrient intakes in the transition phase and postnatal growth of preterm infants: a systematic review - Na Wang; Jia Zhang; Bo Wang; Zhangbin Yu; Jun Zhang; Linlin Qu; Bin Tang (BMC, 2023)
Abstract Nutrition practices for preterm infants include phases of parenteral nutrition, gradually interrupted parenteral nutrition (transition phase), and full enteral nutrition. However, nutrition management during the transition phase is frequently overlooked. This review examined the relationship between nutrient intake during the transition phase and preterm infant growth. PubMed, Embase, Web of Science, Cochrane, Chinese National Knowledge Infrastructure Database, Wanfang Database, and Chinese Science and Technique Journals Database were searched for studies examining the relationship between nutrient intake during the transition phase and postnatal growth of preterm infants from each database's earliest inception through February 28, 2022. The quality of the studies was assessed using the Newcastle-Ottawa scale. A total of three studies conducted in the USA, Italy and China met the inclusion criteria. The growth indicators were extrauterine growth restriction (weight < 10th percentile for post-menstrual age) or inadequate weight growth velocity (growth velocity < 15 g/kg/d) at discharge or the end of the transition phase. The transition phase was divided into two periods in two studies: the early period (parenteral energy intake > 50% of total energy intake) and the late period (enteral energy intake > 50% of the total energy intake). The cumulative protein intake in the transition phase was generally lower in preterm infants with extrauterine growth restriction or inadequate weight growth velocity, especially in the early transition phase. The deficiency of energy and protein intake during the transition phase cannot be explicitly determined due to differences in growth indicators and definitions of the transition phase. However, enteral protein intake should be closely monitored in the early transition phase to ensure a better growth rate for preterm infants. To elucidate potential associations, further well-designed research will be required.